Limit theorems for diffusion-type processes in R^m - Pisanets, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For a sequence of stochastic equations of diffusion type, conditions that are close to necessary and sufficient ones are established for the weak convergence of measures μ _(ξ ^(n) ,w), n = 1, ... , associated with the solutions, to the limiting measure μ _(ξ ^(0) ,w). The conditions under which the weak convergence of the solutions of stochastic equations implies their strong convergence are established as well.